Penerapan Project Based Learning (PJBL) Untuk Meningkatkan Hasil Belajar Siswa Kelas XI MPLB 4 SMK N 7 Medan Pada Materi Drama - Rahel Silalahi; Lukmi Sibarani; Mhd. Isman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
In the implementation of education, an educator must be able to master the class and educate students to master learning. However, not a few teachers are indifferent to the way of teaching and the results obtained by their students. Educators generally use methods that make students often feel bored so that the subject matter is easily forgotten while this can affect a student's learning outcomes. The purpose of this research activity is to determine the effectiveness of the project based learning model in improving the learning outcomes of class XI MPLB 4 SMKN 7 Medan on drama material. The method used was experimental research with a research population of SMK N 7 Medan students and the research sample was 33 students of class XIMPLB 4. The results of individual learning mastery on drama material are seen as indicators of success. In cycle I the 1st meeting obtained individual learning mastery of 27.3%, then the 2nd meeting of 57.6%. In cycle II the 3rd meeting was 72.7%, then the 4th meeting was 90.9% with a value of ≥ 75. The results of the study prove that student learning outcomes can be increased effectively by applying the Project Based Learning learning model.